Research on nitrogen transformation pathways of a thermophilic heterotrophic nitrifying bacterial consortium GW7 - Ma, Yongqi; Wang, Jiali; Zhang, Yindi; Guan, Wenping; Qi, Wenrui; Tai, Xisheng; Lin, Dong; He, Rong; Sun, Likun; Zhang, Aiwen (Frontiers in Microbiology, 2025)
IntroductionHigh-temperature heterotrophic nitrifying bacteria play a crucial role in the thermophilic phase of aerobic composting by effectively converting reduced ammonia sources. This process reduces ammonia emissions and contributes to nitrogen fixation, thus showcasing a high potential for application. The study aims to isolate and characterize a high-temperature-tolerant heterotrophic nitrifying bacterial consortium to enhance nitrogen transformation during aerobic composting.MethodsAn excellent high-temperature-tolerant heterotrophic nitrifying bacterial consortium, designated GW7, was enriched from compost samples at elevated temperatures. The bacterial consortium was cultured under varying conditions to determine optimal cultivation parameters. Response surface methodology (RSM) experiments were conducted to find the best conditions for ammonia and nitrate nitrogen utilization. Enzymatic assays were carried out to measure the specific activities of key enzymes, including glutamine synthetase (GS), glutamate dehydrogenase (GDH), glutamate synthetase (GOGAT), ammonia monooxygenase (AMO), and hydroxylamine oxidoreductase (HAO).ResultsAt 55°C, the GW7 consortium demonstrated a utilization efficiency of 79.97% for ammonia nitrogen (NH₄+-N) (400 mg/L) and 21.18% for nitrate nitrogen (NO₃−-N) (400 mg/L). Response surface methodology identified the optimal cultivation conditions for GW7 as follows: sodium succinate as the carbon source, a C/N ratio of 15:1, a temperature of 53°C, initial pH of 6, and a rotation speed of 200 r/min. Under these conditions, the NH₄+-N utilization efficiency increased to 87.80%. Enzymatic assays showed that the specific activities of GS, GDH, and GOGAT were 0.392 U/mg, 0.926 U/mg, and 0.195 U/mg, respectively. Moreover, the specific activities of AMO and HAO were 1.459 U/mg and 0.701 U/mg, respectively.DiscussionThe GW7 consortium demonstrated excellent nitrogen transformation capabilities, effectively utilizing ammonia nitrogen and contributing to the reduction of nitrogen losses in the aerobic composting process. The high enzymatic activities of key nitrogen-metabolizing enzymes, including AMO and HAO, support its role in heterotrophic nitrification. The proposed nitrogen conversion pathways, including ammonia assimilation, heterotrophic nitrification, and assimilatory nitrate reduction, highlight the versatile nitrogen metabolism of this bacterial consortium. The optimized cultivation conditions further enhance its practical application potential in mitigating nitrogen emissions during composting processes.